Problematic pornography use, body image, and relationship satisfaction among Malaysian young adults - Hen, Zi Wei; Teeba Suriya, Kumar; Wong, Wan Ching (2023)
Malaysia was ranked first in Asia and fourth globally for most visits to porn websites and 51% of the visitors are users aged between 18 to 34 years old. Therefore, the current study focused to look into the association between problematic pornography use with body image dissatisfaction and relationship satisfaction among young adults in romantic relationships in Malaysia. The current study adapted a quantitative research approach through a crosssectional survey design. A purposive sampling method was employed to recruit participants who are self-identified pornography users, individuals between the ages of 18 and 35 who are young adults from Malaysia and in romantic relationships. A total number of 194 participants (M = 20.93 years; SD = 2.25 years), where 93.3% of the participants were Chinese (n=181), were engaged in the current study by responding to an online self-report survey through online platforms and social media. Three instruments were untilized to measure the corresponding variables, including Problematic Pornography Consumption Scale (PPCS), Body Image-Acceptance and Action Questionnaire-5 (BI-AAQ-5), and Relationship Assessment Scale (RAS). The results indicated that problematic pornography use is correlated with increased body image dissatisfaction. In contrast, a non-significant association between problematic pornography use and relationship satisfaction was found. The present findings not only offered a fresh perspective on the existing research about problematic pornography use in Malaysia, but they also contributed empirical evidence to policymakers to create campaigns based on evidence regarding problematic pornography use.